Design And Optimization Of Grid-Connected Single-Phase Residential Photovoltaic System - Salvaragh, Paaventhan Raj (2017)
The ever growing trend of worldwide energy demand and carbon index have driven the efforts to venture into renewable and clean energy efforts. Nations situated along the equator of the earth have been known to venture widely into solar energy as their primary renewable energy due to geographical condition. This is due to locations around the equator line receiving almost constant and high supply of sunlight through- out the year. Due to increase in the implementation of solar energy, multiple designs of photovoltaic power plant have been implemented according to demand needs and financial constraints. In this thesis, the design and optimization concept for grid- connected single-phase smart photovoltaic power plant was established through mod- eling and simulation in MATLAB-Simulink. The design of the photovoltaic power plant included the approach to power sizing the photovoltaic array according to de- mand and environmental parameters. Apart from that, the design also included the selection of the devices such as converters and filter and their respective parameters which fits the objective of the research project precisely. The optimization concept of the photovoltaic power plant included several self-managing smart approaches. One of it is the power flow and grid synchronization approach. Other than that, the sizing and implementation of the automatic power factor correction method and transient mitigation technique through double switching method was also established. These methods are the smart photovoltaic power plant optimization concept to enhance power plant stability and reliability. The simulations were done in two sets of different data. The first set of simulation was to show the power generation and the ability to meet the de- mand according to the trends and fluctuations of solar irradiation and ambient temper- ature. The second set of simulation was the simulation to determine constant average power generation and stability. This simulation was done by using constant parame- ters of solar irradiation and ambient temperature. This set of simulation was also used in determining the efficiency at every stage of the entire plant. The analysis obtained from the simulation results showed the energy generated by the Photovoltaic Power Plant shows to appear that even operating under lower sun hours, a well-planned Pho- tovoltaic Power Plant design manages to meet the power demand with lesser Power Sizing compared to conventional ones improved by 52%. The power plant design and optimization concept was established in ways that power loss throughout the power plant is very small.